Silicon-carbon negative electrode aqueous slurry and preparation method and coating process thereof
By adding antipolymerizer and softener to the silicon-carbon negative electrode water slurry and adopting specific preparation and coating processes, the problem of prone to cracking and powder loss of silicon-carbon negative electrode sheets is solved, achieving the effect of extending the cycle life of lithium-ion batteries.
Patent Information
- Application Number
- CN202510112779.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-03-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Silicon-carbon negative electrode sheets are prone to cracking and powder loss during processing and manufacturing, resulting in a reduced cycle life of lithium-ion batteries.
The toughness and adhesion of the electrode sheet are improved by adding the antipolymerizing agent nitrogen methyl pyrrolidone and the softener vinyl carbonate to the silicon carbon negative electrode aqueous slurry. The specific preparation method and coating process are used.
It effectively solves the problem of prone to cracking and powder loss of silicon carbon negative electrode sheets, and extends the cycle life of lithium-ion batteries.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a silicon-carbon negative electrode aqueous slurry and a preparation method and a coating process thereof. Background Art
[0002] Lithium-ion battery negative electrode materials are mainly divided into two categories: carbon materials and non-carbon materials. Commercial lithium-ion batteries mainly use graphite from carbon materials as negative electrode materials. The theoretical specific capacity of graphite is 372mAh / g. Non-carbon silicon-based negative electrode materials have attracted much attention due to their higher theoretical specific capacity (4200mAh / g). With the advancement of science and technology, silicon-carbon negative electrode materials have gradually been developed. However, in actual application, it was found that although silicon-carbon negative electrode materials have obvious advantages in specific capacity, they have poor compatibility with conventional binders, resulting in poor adhesion between silicon-carbon negative electrode materials and current collectors, and the coating is easy to fall off. Polyacrylic acid (PAA) or lithiated polyacrylic acid (PAA-Li) can significantly improve the adhesion between silicon-carbon negative electrode materials and current collectors, and PAA and PAA-Li also have a certain rigidity, which can effectively inhibit the expansion of silicon in silicon-carbon negative electrode materials to a certain extent. Silicon is prone to volume changes during the charge and discharge process, and the rigidity of PAA or PAA-Li can effectively slow down this volume change, thereby reducing the risk of rupture of the solid electrolyte interface film (SEI film) on the silicon surface. The SEI film is a thin film formed on the electrode surface during the first charge and discharge process of a lithium-ion battery, and its formation consumes a certain amount of lithium ions. PAA or PAA-Li effectively reduces the consumption of lithium ions due to the formation of the SEI film by inhibiting the expansion of silicon and the rupture of the SEI film, which is of great significance for extending the cycle life of silicon-carbon negative electrode lithium-ion batteries.
[0003] However, although PAA or PAA-Li performs well in many aspects, it also has some shortcomings that cannot be ignored. PAA or PAA-Li materials themselves have high rigidity, and are prone to self-polymerization during the homogenization or drying process. This self-polymerization reaction will produce polymers with higher molecular weight, making the pole piece show greater brittleness on a macro scale. This brittleness poses a considerable challenge to the processing of pole pieces and the manufacturing process of batteries. During the processing of pole pieces or the manufacturing of batteries, the pole pieces are prone to cracking or powdering due to external forces. These phenomena not only affect the production efficiency of the battery, but more importantly, they will lead to a reduction in the capacity and cycle life of the battery, thereby limiting the performance of PAA or PAA-Li in practical applications.
[0004] In summary, although PAA or PAA-Li has significant advantages in improving the bonding strength between silicon-carbon negative electrode materials and current collectors and inhibiting silicon expansion, its own high rigidity and easy self-polymerization characteristics also bring certain challenges to battery manufacturing and performance. Therefore, how to solve the cracking and powdering problems caused by binders PAA or PAA-Li during silicon-carbon negative electrode processing or battery manufacturing is the current research direction. Summary of the invention
[0005] The technical problem to be solved by the present invention is: to overcome the shortcomings of the prior art, to provide a silicon-carbon negative electrode aqueous slurry and a preparation method and a coating process thereof, and to solve the problem of easy cracking and powdering of the silicon-carbon negative electrode pole piece by adding an anti-aggregation agent nitrogen methyl pyrrolidone and a softener ethylene carbonate, and matching a suitable preparation method and a coating process, thereby achieving the purpose of extending the cycle life of a silicon-carbon negative electrode lithium-ion battery.
[0006] The technical solution of the present invention is: In a first aspect, the present invention provides a silicon-carbon negative electrode aqueous slurry, comprising a negative electrode active material, a solvent, a conductive agent I, a conductive agent II, a binder, a dispersant, an anti-polymerization agent and a softener, wherein the negative electrode active material is a silicon-carbon negative electrode material, the solvent is deionized water, the conductive agent I is conductive carbon black, the conductive agent II is a single-walled carbon nanotube (SWCNT) aqueous dispersion, the binder is a polyacrylic acid sol (PAA) sol or a lithiated polyacrylic acid (PAA-Li) sol, the dispersant is sodium carboxymethyl cellulose (CMC), the anti-polymerization agent is nitrogen methyl pyrrolidone (NMP), and the softener is ethylene carbonate (EC); the mass ratio of the negative electrode active material, the solvent, the conductive agent I, the solid in the conductive agent II, the solid in the binder, the dispersant, the anti-polymerization agent and the softener is 100: (60-80): (1-1.5): (0.05-0.1): (0.8-1.5): (1-1.2): (5-20): (0.5-0.8).
[0007] Among them, the conductive carbon black can be SP. When the amount of conductive carbon black added is too low, it will lead to poor electronic conductivity of the electrode, while when it is added too high, it will affect the rolling and coating specific capacity of the electrode.
[0008] The role of adding SWCNT is, on the one hand, to act as a conductive agent, and on the other hand, SWCNT overlaps each other in the pole piece, so that the pole piece coating forms a three-dimensional network structure, which can effectively improve the toughness of the pole piece. When the amount of SWCNT added is too low, the pole piece has poor toughness and is easy to break and crack; when the amount added is too high, SWCNT is difficult to disperse and is prone to agglomeration, resulting in poor consistency of pole piece performance, and lithium deposition is prone to occur at the SWCNT agglomeration site, which not only affects the cycle life of the battery, but also poses a major safety hazard.
[0009] The binder PAA sol or PAA-Li sol has a good bonding effect on silicon-based materials and is an ideal binder for silicon-carbon negative electrode materials. Its function is to bond solid particles (including negative electrode active materials and conductive agents) to the current collector. When the amount of binder added is too low, the bonding strength is poor, and it is easy to lose powder, drop material, or separate the coating from the current collector; when the amount added is too high, the pole piece resistance increases, affecting the pole piece capacity and cycle life, and its viscosity is relatively large. If too much is added, it will lead to uneven dispersion of solid particles and poor consistency of pole piece performance.
[0010] CMC acts as a dispersant, making the solid particles evenly dispersed in the silicon-carbon negative electrode water slurry. It also acts as a binder, and works together with the binder PAA sol or PAA-Li sol to make the solid particles in the coating and the coating and the current collector more firmly bonded. When the amount of CMC added is too low, the solid particles in the silicon-carbon negative electrode water slurry have poor dispersibility and the slurry is uneven; when the amount added is too high, the viscosity of the silicon-carbon negative electrode water slurry is too high, which also leads to uneven dispersion of solid particles.
[0011] The principle of NMP as an anti-polymerization agent is that it is miscible with water, but cannot dissolve the binder PAA sol or PAA-Li sol. The binder molecules are dissolved in water containing NMP, and NMP can limit the strong contact between the binder molecules, thereby inhibiting the self-polymerization reaction of the binder.
[0012] There are two reasons for using EC as a softener. On the one hand, its vapor pressure is low and it is not easy to volatilize. It will remain in the electrode after drying, thus softening the electrode. On the other hand, EC is the main component of lithium-ion battery electrolyte, and using EC as a softener will not have a negative impact on the electrolyte.
[0013] Preferably, the silicon-carbon negative electrode material is a CVD vapor-deposited silicon-carbon composite material, a silicon-oxygen-carbon composite material or a nano-silicon-carbon composite material; the silicon content in the silicon-carbon negative electrode material is 0.5-10wt.%.
[0014] Preferably, the content of the single-walled carbon nanotubes in the single-walled carbon nanotube aqueous dispersion is 0.4-1 wt.%.
[0015] Preferably, the solid content of the polyacrylic acid sol or the lithiated polyacrylic acid sol is 6-10 wt.%.
[0016] Preferably, the degree of substitution of sodium carboxymethyl cellulose is 0.6-0.85. If the degree of substitution of sodium carboxymethyl cellulose is too low, the bonding performance is poor; while if the degree of substitution is too high, the viscosity is too high and the dispersibility is poor.
[0017] Preferably, the viscosity of the silicon-carbon negative electrode aqueous slurry is 8000-12000 mPa·s. When the viscosity of the silicon-carbon negative electrode aqueous slurry is too low, it is easy to settle, resulting in poor consistency of the electrode sheet and poor bonding strength between the coating and the current collector; when the viscosity is too high, the solid particles are unevenly dispersed in the silicon-carbon negative electrode aqueous slurry, which also leads to poor consistency of the electrode sheet.
[0018] In a second aspect, the present invention provides a method for preparing the above-mentioned silicon-carbon negative electrode aqueous slurry, comprising the following steps: S1 dissolving sodium carboxymethyl cellulose: adding 90-95wt.% of solvent to the homogenizing tank of the homogenizer, and then adding sodium carboxymethyl cellulose, and stirring to obtain sodium carboxymethyl cellulose sol; S2 Add anti-polymerization agent and softener: dissolve the softener in the anti-polymerization agent, add to the homogenization tank and stir; S3 Adding binder: Adding binder into the homogenizing tank and continuing to stir; S4 Adding conductive agent II: Add conductive agent II into the homogenizing tank and continue stirring; S5: adding the negative electrode active material and the conductive agent I: adding the negative electrode active material and the conductive agent I into the homogenizing tank and continuing to stir; S6 Add the remaining solvent into the homogenization tank.
[0019] Preferably, in step S1, the speed of the homogenizer stirrer is 15-25rpm, the speed of the disperser is 3000-4000rpm, the temperature in the homogenizer tank is 25-60°C, and the stirring time is 180-240min; in step S2, the speed of the homogenizer stirrer is 15-25rpm, the speed of the disperser is 3000-4000rpm, the temperature in the homogenizer tank is 25-60°C, and the stirring time is 30-60min. If the stirrer speed is too low or too high, the probability and time of contact between the CMC sol and the disperser will be reduced, and the homogenization time will be prolonged. When the disperser speed is too low, the shear force formed is small, which is not conducive to the dispersion and dissolution of the CMC sol; if the speed is too high, the molecular structure of CMC will be damaged, causing part of the CMC to degrade and fail. If the temperature in the homogenizer tank is too low, it is not conducive to the dissolution of CMC and will prolong the sol time; if the temperature is too high, it will cause CMC to degrade and fail.
[0020] Preferably, in steps S3, S4 and S5, the speed of the homogenizer stirrer is 15-25rpm, the speed of the disperser is 3000-4000rpm, the temperature in the homogenizer tank is 15-35°C, and the stirring time is 60-120min. In step S3, if the temperature in the homogenizer tank is too low, the various polymer substances in the slurry are not active, which affects the uniformity of the slurry; if the temperature is too high, the binder will undergo self-polymerization before being fully dispersed. In addition, since the viscosity of the binder PAA sol or PAA-Li sol is relatively high, it is relatively difficult to disperse in the slurry. Therefore, when the stirring time is too short, it is unevenly dispersed in the slurry. When the pole piece is dried, the PAA or PAA-Li will undergo self-polymerization reaction where a large number of aggregations are formed, resulting in greater local brittleness of the pole piece.
[0021] In a third aspect, the present invention provides a coating process of the above-mentioned silicon-carbon negative electrode aqueous slurry, comprising the following steps: (1) coating the silicon-carbon negative electrode aqueous slurry on copper foil, and then drying it at 70-80°C for 2-3 minutes; (2) Then dry at 90-95°C for 2-3 minutes; (3) Finally, dry at 100-105°C for 2-3 minutes to complete the coating of the silicon-carbon negative electrode aqueous slurry.
[0022] The coating process of the silicon-carbon negative electrode aqueous slurry of the present invention is divided into three stages, the first stage is surface drying, the second stage is water removal, and the third stage is the removal of the anti-polymerization agent NMP. Among them, the first stage uses a lower drying temperature to dry the coating surface. The lower drying temperature can make the coating form a crack-free surface in good condition. The dry film formed on the surface has high mechanical strength and can inhibit the destructive effect of the stress generated by subsequent high-temperature drying on the coating. When the drying temperature is too low or the drying time is too short, the dry film formed on the surface does not play a role in protecting the coating; when the temperature is too high, it will cause the drying speed to be too fast and cracks to form on the coating surface. The second stage is mainly to control the drying temperature and drying time so that the water in the coating evaporates first, and most of the NMP remains in the coating to inhibit the self-polymerization reaction of PAA or PAA-Li under high temperature. When the drying temperature of the second stage is too low or the drying time is too short, it will lead to insufficient removal of water in the subsequent drying, affecting the adhesion between the coating and the current collector; when the drying temperature is too high, it will cause a large amount of EC to volatilize and fail to soften the pole piece. The third stage is to remove the anti-polymerization agent NMP in the coating. NMP is an organic solvent. If it is not completely removed, it will damage the positive electrode coating. When the drying temperature in the third stage is too low or the drying time is too short, NMP is not fully removed; when the drying temperature is too high or the drying time is too long, EC will evaporate in large quantities, reducing the softening effect on the electrode.
[0023] Compared with the prior art, the present invention has the following beneficial effects: The present invention solves the problem of easy cracking and powdering of silicon-carbon negative electrode plates by adding an anti-aggregation agent nitrogen-methyl pyrrolidone and a softener ethylene carbonate, matching a suitable preparation method and a coating process, thereby achieving the purpose of extending the cycle life of silicon-carbon negative electrode lithium-ion batteries. DETAILED DESCRIPTION
[0024] In order to enable persons skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.
[0025] The sources of raw materials used in the following examples and comparative examples are as follows: PAA sol, PAA-Li sol: Shenzhen Yanyi New Materials Co., Ltd.; SWCNT: Shenyang East Chemical Technology Co., Ltd.; CVD vapor deposition silicon-carbon composite material: SC2A-600, Liyang Tianmu Pioneer Battery Material Technology Co., Ltd.; Silicon-oxygen-carbon composite material: DXA8, BTR New Materials Group Co., Ltd.; Nano-silicon-carbon composite material: S400, BTR New Materials Group Co., Ltd.
[0026] Example 1 The formula of the silicon-carbon negative electrode aqueous slurry of this embodiment is shown in Table 1.
[0027] The method for preparing the silicon-carbon negative electrode aqueous slurry of this embodiment comprises the following steps: S1 dissolves sodium carboxymethyl cellulose: add 720g of deionized water to the homogenizing tank of the homogenizer, then add 10g of CMC with a degree of substitution of 0.6, the speed of the homogenizer stirrer is 15rpm, the speed of the disperser is 3000rpm, the temperature in the homogenizing tank is 25°C, the stirring time is 180min, and the sodium carboxymethyl cellulose sol is obtained after stirring; S2 Add anti-polymerization agent and softener: Dissolve 5g EC in 50g NMP, add to the homogenizer and continue stirring. The speed of the homogenizer stirrer is 15rpm, the speed of the disperser is 3000rpm, the temperature in the homogenizer is 25℃, and the stirring time is 30min. S3 Adding binder: Add 133.3 g of PAA sol (including 8 g of PAA solid) into the homogenizer and continue stirring. The speed of the homogenizer stirrer is 15 rpm, the speed of the disperser is 3000 rpm, the temperature in the homogenizer is 15 ° C, and the stirring time is 60 min; S4 Adding conductive agent II: Add 125 g of SWCNT aqueous dispersion (containing 0.5 g of SWCNT solid) into the homogenizer and continue stirring. The speed of the homogenizer stirrer is 15 rpm, the speed of the disperser is 3000 rpm, the temperature in the homogenizer is 15 ° C, and the stirring time is 60 min; S5 Adding negative electrode active material and conductive agent I: Add 1000g of CVD vapor deposition silicon-carbon composite material SC2A-600 (silicon content is 8wt.%) and 10g of conductive carbon black SP into the homogenizing tank and continue stirring. The speed of the homogenizer stirrer is 15rpm, the speed of the disperser is 3000rpm, the temperature in the homogenizing tank is 15℃, and the stirring time is 60min. S6: Add the remaining 80 g of deionized water into the homogenization tank and adjust the viscosity of the silicon-carbon negative electrode aqueous slurry to 8000 mPa·s.
[0028] The coating process of the silicon-carbon negative electrode aqueous slurry of this embodiment includes the following steps: (1) Coating the silicon-carbon negative electrode aqueous slurry on the copper foil, and then placing it in an oven and drying it at 70°C for 3 minutes; (2) Then dry at 90°C for 3 min; (3) Finally, the mixture is dried at 100°C for 3 minutes to complete the coating of the silicon-carbon negative electrode aqueous slurry.
[0029] Example 2 The formula of the silicon-carbon negative electrode aqueous slurry of this embodiment is shown in Table 1.
[0030] The method for preparing the silicon-carbon negative electrode aqueous slurry of this embodiment comprises the following steps: S1 dissolving sodium carboxymethyl cellulose: add 570g of deionized water to the homogenizing tank of the homogenizer, then add 12g of CMC with a degree of substitution of 0.85, the speed of the homogenizer stirrer is 25rpm, the speed of the disperser is 4000rpm, the temperature in the homogenizing tank is 60°C, the stirring time is 240min, and the sodium carboxymethyl cellulose sol is obtained after stirring; S2 Add anti-polymerization agent and softener: dissolve 8g EC in 200g NMP, add to the homogenizer and continue stirring, the homogenizer stirrer speed is 25rpm, the disperser speed is 4000rpm, the temperature in the homogenizer is 60℃, and the stirring time is 60min; S3 Adding binder: Add 200g of PAA sol (containing 15g of PAA solid) into the homogenizing tank and continue stirring. The speed of the homogenizer stirrer is 25rpm, the speed of the disperser is 4000rpm, the temperature in the homogenizing tank is 35℃, and the stirring time is 120min. S4 Adding conductive agent II: Add 170 g of SWCNT aqueous dispersion (containing 1 g of SWCNT solid) into the homogenizer and continue stirring. The speed of the homogenizer stirrer is 25 rpm, the speed of the disperser is 4000 rpm, the temperature in the homogenizer is 35 ° C, and the stirring time is 120 min. S5 Adding negative electrode active material and conductive agent I: Add 1000g of silicon-oxygen-carbon composite material DXA8 (silicon content is 10wt.%) and 15g of conductive carbon black SP into a homogenizing tank and continue stirring. The speed of the homogenizer stirrer is 25rpm, the speed of the disperser is 4000rpm, the temperature in the homogenizing tank is 35℃, and the stirring time is 120min. S6: Add the remaining 30 g of deionized water into the homogenization tank and adjust the viscosity of the silicon-carbon negative electrode aqueous slurry to 12000 mPa·s.
[0031] The coating process of the silicon-carbon negative electrode aqueous slurry of this embodiment includes the following steps: (1) Coating the silicon-carbon negative electrode aqueous slurry on the copper foil, and then placing it in an oven and drying it at 80°C for 2 minutes; (2) Then dry at 95°C for 2 min; (3) Finally, the coating is completed by drying at 105°C for 2 minutes.
[0032] Example 3 The formula of the silicon-carbon negative electrode aqueous slurry of this embodiment is shown in Table 1.
[0033] The method for preparing the silicon-carbon negative electrode aqueous slurry of this embodiment comprises the following steps: S1 dissolving sodium carboxymethyl cellulose: add 650g of deionized water to the homogenizing tank of the homogenizer, then add 11g of CMC with a degree of substitution of 0.75, the speed of the homogenizer stirrer is 20rpm, the speed of the disperser is 3500rpm, the temperature in the homogenizing tank is 40°C, the stirring time is 210min, and the sodium carboxymethyl cellulose sol is obtained after stirring; S2 Add anti-polymerization agent and softener: Dissolve 6.5g EC in 125g NMP, add to the homogenizer and continue stirring. The speed of the homogenizer stirrer is 20rpm, the speed of the disperser is 3500rpm, the temperature in the homogenizer is 40℃, and the stirring time is 45min. S3 Adding binder: Add 120g of PAA-Li sol (containing 12g of PAA-Li solid) into the homogenizing tank and continue stirring. The speed of the homogenizer stirrer is 20rpm, the speed of the disperser is 3500rpm, the temperature in the homogenizing tank is 25℃, and the stirring time is 90min. S4 Adding conductive agent II: Add 75 g of SWCNT aqueous dispersion (containing 0.75 g of SWCNT solid) into the homogenizer and continue stirring. The speed of the homogenizer stirrer is 20 rpm, the speed of the disperser is 3500 rpm, the temperature in the homogenizer is 25 ° C, and the stirring time is 90 min; S5 Add negative electrode active material and conductive agent I: Add 1000g of nano silicon-carbon composite material S400 (silicon content is 0.5wt.%) and 12.5g of conductive carbon black SP into the homogenizing tank and continue stirring. The speed of the homogenizer stirrer is 20rpm, the speed of the disperser is 3500rpm, the temperature in the homogenizing tank is 25℃, and the stirring time is 90min. S6: Add the remaining 50 g of deionized water into the homogenization tank and adjust the viscosity of the silicon-carbon negative electrode aqueous slurry to 10,000 mPa·s.
[0034] The coating process of the silicon-carbon negative electrode aqueous slurry of this embodiment includes the following steps: (1) Coating the silicon-carbon negative electrode aqueous slurry on the copper foil, and then placing it in an oven and drying it at 75°C for 3 minutes; (2) Then dry at 92.5°C for 3 min; (3) Finally, the coating of the silicon-carbon negative electrode aqueous slurry is completed by drying at 102.5°C for 3 minutes.
[0035] Comparative Example 1 The formula of the silicon-carbon negative electrode aqueous slurry of Comparative Example 1 is shown in Table 1.
[0036] The method for preparing the silicon-carbon negative electrode aqueous slurry of Comparative Example 1 comprises the following steps: S1 dissolves sodium carboxymethyl cellulose: add 640g of deionized water to the homogenizer tank, then add 8g of CMC with a degree of substitution of 0.6, the speed of the homogenizer stirrer is 15rpm, the speed of the disperser is 3000rpm, the temperature in the homogenizer tank is 25°C, the stirring time is 180min, and the sodium carboxymethyl cellulose sol is obtained after stirring; S2 Add anti-polymerization agent and softener: Dissolve 4g EC in 40g NMP, add to the homogenizer and continue stirring. The speed of the homogenizer stirrer is 15rpm, the speed of the disperser is 3000rpm, the temperature in the homogenizer is 25℃, and the stirring time is 30min. S3 Adding binder: Add 100g of PAA sol (containing 6g of PAA solid) into the homogenizing tank and continue stirring. The speed of the homogenizer stirrer is 15rpm, the temperature in the homogenizing tank is 15℃, and the stirring time is 60min. S4 Adding conductive agent II: Add 100 g of SWCNT aqueous dispersion (containing 0.4 g of SWCNT solid) into the homogenizing tank and continue stirring. The speed of the homogenizer stirrer is 15 rpm, the temperature in the homogenizing tank is 15 °C, and the stirring time is 60 min. S5 Add negative electrode active material and conductive agent I: Add 1000g of CVD vapor deposition silicon-carbon composite material SC2A-600 (silicon content is 8wt.%) and 8g of conductive carbon black SP into the homogenizing tank and continue stirring. The speed of the homogenizer stirrer is 15rpm, the temperature in the homogenizing tank is 15℃, and the stirring time is 60min. S6: Add the remaining 160 g of deionized water into the homogenization tank and adjust the viscosity of the silicon-carbon negative electrode aqueous slurry to 6000 mPa·s.
[0037] The coating process of the silicon-carbon negative electrode aqueous slurry of Comparative Example 1 is the same as that of Example 1.
[0038] Comparative Example 2 The formula of the silicon-carbon negative electrode aqueous slurry of Comparative Example 2 is shown in Table 1.
[0039] The preparation method of the silicon-carbon negative electrode aqueous slurry of Comparative Example 2 comprises the following steps: S1 dissolves sodium carboxymethyl cellulose: add 600g of deionized water to the homogenizing tank of the homogenizer, then add 15g of CMC with a degree of substitution of 0.6, the speed of the homogenizer stirrer is 15rpm, the speed of the disperser is 3000rpm, the temperature in the homogenizing tank is 25°C, the stirring time is 180min, and the sodium carboxymethyl cellulose sol is obtained after stirring; S2 Add anti-polymerization agent and softener: Dissolve 10g EC in 250g NMP, add to the homogenizer and continue stirring. The speed of the homogenizer stirrer is 15rpm, the speed of the disperser is 3000rpm, the temperature in the homogenizer is 25℃, and the stirring time is 30min. S3 Adding binder: Add 333 g of PAA sol (containing 20 g of PAA solid) into the homogenizing tank and continue stirring. The speed of the homogenizer stirrer is 15 rpm, the temperature in the homogenizing tank is 15°C, and the stirring time is 60 min. S4 Adding conductive agent II: Add 375 g of SWCNT aqueous dispersion (containing 1.5 g of SWCNT solid) into the homogenizing tank and continue stirring. The speed of the homogenizer stirrer is 15 rpm, the temperature in the homogenizing tank is 15 °C, and the stirring time is 60 min. S5 Add negative electrode active material and conductive agent I: Add 1000g of CVD vapor deposition silicon-carbon composite material SC2A-600 (silicon content is 8wt.%) and 18g of conductive carbon black SP into the homogenizing tank and continue stirring. The speed of the homogenizer stirrer is 15rpm, the temperature in the homogenizing tank is 15℃, and the stirring time is 60min. S6: Add the remaining 160 g of deionized water into the homogenization tank and adjust the viscosity of the silicon-carbon negative electrode aqueous slurry to 14000 mPa·s.
[0040] The coating process of the silicon-carbon negative electrode aqueous slurry of Comparative Example 2 is the same as that of Example 1.
[0041] Comparative Example 3 The difference from Example 1 is that in step S2, no softener EC is added. The formula of the silicon-carbon negative electrode aqueous slurry of Comparative Example 3 is shown in Table 1.
[0042] Comparative Example 4 The difference from Example 1 is that in step S2, no anti-polymerization agent NMP is added. The formula of the silicon-carbon negative electrode aqueous slurry of Comparative Example 4 is shown in Table 1.
[0043] Comparative Example 5 The difference from Example 1 is that in step (1), the drying temperature is 85° C. The formula of the silicon-carbon negative electrode aqueous slurry of Comparative Example 5 is shown in Table 1.
[0044] Comparative Example 6 The difference from Example 1 is that in step (2), the drying temperature is 100° C. The formula of the silicon-carbon negative electrode aqueous slurry of Comparative Example 6 is shown in Table 1.
[0045] Comparative Example 7 The difference from Example 1 is that in step (3), the drying temperature is 110° C. The formula of the silicon-carbon negative electrode aqueous slurry of Comparative Example 7 is shown in Table 1.
[0046] Table 1 Silicon-carbon negative electrode aqueous slurry formula of Examples 1-3 and Comparative Examples 1-7
[0047] The coatings formed after coating the silicon-carbon negative electrode aqueous slurry of Examples 1-3 and Comparative Examples 1-7 were bent at 45° using a flexibility tester (Tianjin Jinghai Kexin Testing Machine Factory, QTY-32 model) to visually inspect whether they were cracked. The test results are shown in Table 2.
[0048] The copper foil coated with the silicon-carbon negative electrode aqueous slurry in Examples 1-3 and Comparative Examples 1-7 was used as the negative electrode sheet. The negative electrode sheet had a size of 83 mm × 98 mm and a double-sided coating surface density of 18 mg / cm 2, assemble a CR2032 half-cell, charge it to a voltage of 0.01V, and test the discharge capacity of the negative electrode active material. The test results are shown in Table 2. The above negative electrode plate and the positive electrode plate with the active material M2-C2 are combined into a full battery with a 10 positive and 11 negative structure, with an N / P ratio of 1.1:1. The full battery is charged to 4.25V at 0.5C constant current, then charged to 0.05C at a constant voltage, and then discharged to 2.75V at 1C constant current. The cycle performance of the full battery is tested for 500 times. The test results are shown in Table 2.
[0049] Table 2 Test results of coating cracking, discharge capacity of half-cell negative electrode active material and cycle performance of full cell in Examples 1-3 and Comparative Examples 1-7
[0050] As can be seen from Table 2, by using the silicon-carbon negative electrode aqueous slurry and coating process of the present invention, the cracking and falling of the prepared negative electrode sheet are solved, and the negative electrode active material in the negative electrode sheet exhibits high discharge specific capacity and high cycle life. The surface of the negative electrode sheet prepared in Comparative Example 1-2 showed cracks and edge falling, and the discharge specific capacity and cycle life of the negative electrode active material were also significantly reduced. It can be seen that the ratio of each component in the silicon-carbon negative electrode aqueous slurry is crucial to the performance of the negative electrode sheet.
[0051] In addition, it can be seen from Comparative Example 3 that when the softener EC is not added to the silicon-carbon negative electrode aqueous slurry, the prepared negative electrode plate has more cracks and more serious edge dropout. At the same time, compared with Example 1, the active material discharge specific capacity and cycle life are greatly reduced. This is because although the anti-polymerization agent NMP is added to the silicon-carbon negative electrode aqueous slurry to prevent the self-polymerization reaction of PAA, the PAA molecule itself has strong rigidity. When the softener EC is not added, the pole piece is still brittle. The cracks on the pole piece affect the uniform distribution of the current on the pole piece, resulting in a decrease in the discharge specific capacity of the active material; during the cycle, the active material will have a certain volume expansion. As the cycle progresses, the cracks on the pole piece and the edge dropout are very likely to fall off due to the volume expansion of the active material, resulting in a decrease in the cycle life.
[0052] It can be seen from Comparative Example 4 that when the anti-polymerization agent NMP is not added to the silicon-carbon negative electrode aqueous slurry, the prepared negative electrode plate has many cracks and serious edge shedding, and the discharge capacity and cycle life of the active material are seriously reduced. This is because, on the one hand, NMP can play an anti-polymerization role, and when NMP is not added, PAA will undergo self-polymerization during the homogenization and plate drying process to form larger molecules, and the macroscopic brittleness increases; on the other hand, EC is insoluble in deionized water and cannot be dispersed in the slurry, so EC cannot be evenly dispersed in the silicon-carbon negative electrode aqueous slurry, which ultimately leads to serious cracks and shedding of the plate, which makes the discharge capacity and cycle life of the active material decline more seriously.
[0053] It can be seen from Comparative Example 5 that when the silicon-carbon negative electrode aqueous slurry is applied, the drying temperature in the first stage is too high, which will cause more cracks and more serious edge shedding of the pole piece, and the discharge capacity and cycle life of the active material will be seriously reduced. This is because when the drying temperature in step (1) is too high, the deionized water evaporates too quickly, resulting in the stress generated during the drying process of the pole piece cannot be released in time, resulting in more serious cracks and shedding of the pole piece, causing the active material and cycle life to be seriously reduced. It can be seen from Comparative Examples 6-7 that the drying temperature in the second and third stages is too high, which will cause cracks and edge shedding of the pole piece, and the discharge capacity and cycle life of the active material will be reduced. This is because the temperature in steps (2) and (3) is too high, which will cause a large amount of EC to volatilize, and the remaining small amount of EC will weaken the softening effect on the pole piece, resulting in cracks and shedding of the pole piece, which will reduce the discharge capacity and cycle life of the active material.
[0054] In summary, the negative electrode sheet obtained by adopting the silicon-carbon negative electrode aqueous slurry formulation, preparation method and coating process of the present invention can effectively solve the problems of cracking and falling of negative electrode active materials in existing negative electrode sheets, and improve the discharge specific capacity and cycle life of negative electrode active materials.
Claims
1. A silicon-carbon negative electrode aqueous slurry, characterized in that: The invention comprises a negative electrode active material, a solvent, a conductive agent I, a conductive agent II, a binder, a dispersant, an anti-polymerization agent and a softener. The negative electrode active material is a silicon-carbon negative electrode material, the solvent is deionized water, the conductive agent I is conductive carbon black, the conductive agent II is a single-walled carbon nanotube aqueous dispersion, the binder is polyacrylic acid sol or lithiated polyacrylic acid sol, the dispersant is sodium carboxymethyl cellulose, the anti-polymerization agent is nitrogen methyl pyrrolidone, and the softener is ethylene carbonate; the mass ratio of the negative electrode active material, the solvent, the conductive agent I, the solid in the conductive agent II, the solid in the binder, the dispersant, the anti-polymerization agent and the softener is 100: (60-80): (1-1.5): (0.05-0.1): (0.8-1.5): (1-1.2): (5-20): (0.5-0.8).
2. The silicon-carbon negative electrode aqueous slurry according to claim 1, characterized in that: The silicon-carbon negative electrode material is a CVD vapor-deposited silicon-carbon composite material, a silicon-oxygen-carbon composite material or a nano-silicon-carbon composite material; the silicon content in the silicon-carbon negative electrode material is 0.5-10wt.%.
3. The silicon-carbon negative electrode aqueous slurry according to claim 1, characterized in that: The content of the single-walled carbon nanotubes in the single-walled carbon nanotube aqueous dispersion is 0.4-1 wt.%.
4. The silicon-carbon negative electrode aqueous slurry according to claim 1, characterized in that: The solid content of the polyacrylic acid sol or the lithiated polyacrylic acid sol is 6-10 wt.%.
5. The silicon-carbon negative electrode aqueous slurry according to claim 1, characterized in that: The degree of substitution of sodium carboxymethyl cellulose is 0.6-0.
85.
6. The silicon-carbon negative electrode aqueous slurry according to claim 1, characterized in that: The viscosity of the silicon-carbon negative electrode aqueous slurry is 8000-12000mPa·s.
7. The method for preparing the silicon-carbon negative electrode aqueous slurry according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1 dissolving sodium carboxymethyl cellulose: adding 90-95wt.% of solvent to the homogenizing tank of the homogenizer, and then adding sodium carboxymethyl cellulose, and stirring to obtain sodium carboxymethyl cellulose sol; S2 Add anti-polymerization agent and softener: dissolve the softener in the anti-polymerization agent, add to the homogenization tank and stir; S3 Adding binder: Adding binder into the homogenizing tank and continuing to stir; S4 Adding conductive agent II: Add conductive agent II into the homogenizing tank and continue stirring; S5: adding the negative electrode active material and the conductive agent I: adding the negative electrode active material and the conductive agent I into the homogenizing tank and continuing to stir; S6 Add the remaining solvent into the homogenization tank.
8. The method for preparing the silicon-carbon negative electrode aqueous slurry according to claim 7, characterized in that: In step S1, the speed of the homogenizer stirrer is 15-25rpm, the speed of the disperser is 3000-4000rpm, the temperature in the homogenizer tank is 25-60°C, and the stirring time is 180-240min; in step S2, the speed of the homogenizer stirrer is 15-25rpm, the speed of the disperser is 3000-4000rpm, the temperature in the homogenizer tank is 25-60°C, and the stirring time is 30-60min.
9. The method for preparing the silicon-carbon negative electrode aqueous slurry according to claim 7, characterized in that: In steps S3, S4 and S5, the speed of the homogenizer stirrer is 15-25 rpm, the speed of the disperser is 3000-4000 rpm, the temperature in the homogenizer tank is 15-35° C., and the stirring time is 60-120 min.
10. The coating process of the silicon-carbon negative electrode aqueous slurry according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) coating the silicon-carbon negative electrode aqueous slurry on copper foil, and then drying it at 70-80°C for 2-3 minutes; (2) Then dry at 90-95°C for 2-3 minutes; (3) Finally, dry at 100-105°C for 2-3 minutes to complete the coating of the silicon-carbon negative electrode aqueous slurry.
Citation Information
Patent Citations
Silicon-carbon composite cathode pole piece of lithium ion battery and preparation method of silicon-carbon composite cathode pole piece
CN105576185A
Composite binder, silicon-based negative electrode plate and preparation method thereof
CN110350196A
Silicon-carbon negative electrode slurry mixing method
CN111313005A
Preparation method of carbon-silicon negative electrode slurry, carbon-silicon negative electrode slurry and lithium ion battery
CN114242992A
Negative pole piece, preparation method thereof and battery
CN119297206A